Do Alterations in Soil Physical Attributes Resulting from Chiseling Persist after Sugarcane Planting?. Issue 4 (21st February 2022) - de Souza, Francisco Carlos Almeida; Fernandes, Mariele Monique Honorato; Coelho, Anderson Prates; Pinheiro, Daniel Pereira; Perecin, Dilermando; Fernandes, Carolina
ABSTRACT: Soil tillage is a high-cost operation in the replanting of sugarcane fields. Thus, measures to reduce this cost are desirable, provided that they promote good physical conditions for sugarcane development. The objective of this study was to evaluate the effect of chiseling in total area and in the planting row on the physical attributes of Oxisol and Ultisol after soil tillage and after sugarcane planting. The experimental design was in large and uniform plots, with two treatments and ten replicates. The Oxisol and Ultisol had clay contents of 590 and 168 g kg −1 in the 0.00–0.40 cm layer. Treatments consisted of soil tillage with chiseling in the planting row and with chiseling in total area. After soil chiseling and after planting, undisturbed soil samples were collected in each experimental plot, in three layers (0.00–0.10; 0.10–0.20 and 0.20–0.40 m) and at two sampling sites (row and interrow). In both soils, chiseling in total area was efficient to reduce soil density and increase macroporosity in sugarcane interrows, compared to chiseling in the row. The values of the physical attributes of the soils evaluated, in rows and interrows, were similar in the areas with chiseling in total area and row chiseling after sugarcane planting. Changes in Oxisol and Ultisol structure due to chiseling did not persist after sugarcane planting. The soil under row chiseling system has physical quality similar to that of the soil under total area chiseling system, regardless of texture.